A proteogenomic atlas of the human neural retina - Riepe, Tabea V.; Stemerdink, Merel; Salz, Renee; Rey, Alfredo Dueñas; de Bruijn, Suzanne E.; Boonen, Erica; Tomkiewicz, Tomasz Z.; Kwint, Michael; Gloerich, Jolein; Wessels, Hans J. C. T.; Delanote, Emma; De Baere, Elfride; et al. (Frontiers in Genetics, 2024)
The human neural retina is a complex tissue with abundant alternative splicing and more than 10% of genetic variants linked to inherited retinal diseases (IRDs) alter splicing. Traditional short-read RNAsequencing methods have been used for understanding retina-specific splicing but have limitations in detailing transcript isoforms. To address this, we generated a proteogenomic atlas that combines PacBio long-read RNA-sequencing data with mass spectrometry and whole genome sequencing data of three healthy human neural retina samples. We identified nearly 60,000 transcript isoforms, of which approximately one-third are novel. Additionally, ten novel peptides confirmed novel transcript isoforms. For instance, we identified a novel IMPDH1 isoform with a novel combination of known exons that is supported by peptide evidence. Our research underscores the potential of in-depth tissue-specific transcriptomic analysis to enhance our grasp of tissue-specific alternative splicing. The data underlying the proteogenomic atlas are available via EGA with identifier EGAD50000000101, via ProteomeXchange with identifier PXD045187, and accessible through the UCSC genome browser.